The association between anti‐acetylcholine receptor antibody level and clinical improvement in myasthenia gravis. (9th January 2022) - Marcuse, Florit; Brandts, Lloyd; Moens, Daan; Damoiseaux, Jan; Hochstenbag, Monique; Hoeijmakers, Janneke G. J.; Maessen, Jos G.; De Baets, Marc
Abstract: Background and purpose: Anti‐acetylcholine receptor (AChR) antibodies (ab) in the serum are detected in most patients with generalized myasthenia gravis (MG) and used as a diagnostic tool. The aim of this study was to analyse a possible association between anti‐AChR‐ab serum levels and clinical improvement of MG. Methods: The Maastricht University Medical Center is a centre of expertise for the treatment of MG. Between 1997 and 2020, more than 4000 anti‐AChR‐ab blood samples were measured for clinical care using a quantitative radioimmunoassay technique. These results, in combination with clinical status obtained from the patients' electronic patient files, were retrospectively analysed by a single blinded clinician. Symptoms of MG were classified using the Myasthenia Gravis Foundation of America (MGFA) scale. Results: In total, 90 anti‐AChR‐ab‐positive MG patients with 837 blood samples were included. The median follow‐up time was 72 months. The majority of the included patients were women (61.1%), were on immunosuppressive drug therapy (88.9%), and underwent a thymectomy (54.4%). Multilevel logistic regression analysis showed a significantly inverse association between change in anti‐AChR‐ab level and the odds of MGFA improvement (per 10% decrease of anti‐AChR‐ab level: odds ratio 1.21, 95% confidence interval 1.12–1.31; p  < 0.001). Conclusions: A change in anti‐AChR‐ab serum level is associated with clinical status in patients with MG. Analyses of anti‐AChR‐ab are not only useful for diagnostics but also in follow‐up of adult symptomatic patients with MG. The use of repetitive anti‐AChR‐ab serum levels might be valuable in long‐term monitoring for clinical improvement in patients with MG, however, further research is required for specific recommendations. Abstract : Multilevel logistic regression analysis showed a significant inverse association between change in anti‐acetylcholine receptor (AchR) antibody (ab) level and the odds of improvement, measured by the Myasthenia Gravis Foundation of America. A change in anti‐AChR‐ab serum level is associated with clinical status in patients with MG. Repetitive measurements of anti‐AChR‐ab serum levels can objectively assist in the follow‐up of a patient with MG.